Altered Populations of Unconventional T Cell Lineages in Patients with Langerhans Cell Histiocytosis. Issue 1 (December 2018) - Mitchell, Jenée; Kvedaraite, Egle; von Bahr Greenwood, Tatiana; Henter, Jan-Inge; Pellicci, Daniel; Berzins, Stuart; Kannourakis, George
Abstract Langerhans cell histiocytosis (LCH) lesions are defined by the presence of CD1a+ /CD207+ myeloid cells, but many other immune cells are present including unconventional T cells, which have powerful immunoregulatory functions. Unconventional T cell lineages include mucosal-associated invariant T (MAIT) cells, type I natural killer T (NKT) cells and gamma-delta (γδ) T cells, which are associated with many inflammatory conditions, although their importance has not been studied in LCH. We characterized their phenotype and function in blood and lesions from patients with LCH, and identified a deficiency in MAIT cell frequency and abnormalities in the subset distributions of γδ T cells and NKT cells. Such abnormalities are associated with immune dysregulation in other disease settings and are therefore potentially important in LCH. Our study is the first to recognize alterations to MAIT cell proportions in patients with LCH. This finding along with other abnormalities identified amongst unconventional T cells could potentially influence the onset and progression of LCH, thereby highlighting potential targets for new immune based therapies.